Problem razdvojenega subjekta v delih Marjana Rožanca - Štuhec, Miran (Jezik in slovstvo, 2014)
After a short argumentation of the content, we synthetically highlight some of the main characteristics of Rožanc's writing. Our interest is largely focused on his essays, as they reveal the most important characteristics of the author's absorbed and subtle relationship towards the world. Through the notion of split character, the author furnished the basis of questions dealing with God and mankind, man and woman, games and sport, art and creativity, with a constant search for equilibrium and meaning.
Keywords: Rožanc, Marjan, 1930-1990; slovenski esej; razdvojeni subjekt; humanism; humanizem; hominizacija; paradoksalna eksistenca; iskanje boga